Microwave Assisted Synthesis and Characterization of Some New Isatin Derivatives - Patel, Ankur; Bari, S.B.; Talele, G.S.; Patel, J.S. (Asian Journal of Chemistry, 2010)
3-[(5-Benzylidene-2-phenyl)-3,5-dihydro-4H-imidazol-4-one-3-(4-benzoylhydrazono)]- indole-2-ones (IV) were synthesized in high yield (82%) using a microwave method. In these, different isatin hydrazones (II) are reacted with 2-phenyl-5 bezylidene-3-N-(4-acetyl phenyl)-1,5-dihydro-imidazol-4-one to afford final compound (IV). Synthesis of 3-[(5- benzylidene-2-phenyl)-3,5 dihydro-4H-imidazol-4-one-3-(4-benzoyl hydrazono)]- indole-2- ones (IV) was found much easier and faster than conventional heating method. These compounds were characterized by IR, 1H NMR and mass spectra.